2013
DOI: 10.5194/nhess-13-193-2013
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication "Further comments on the ionospheric precursor of the 1999 Hector Mine earthquake"

Abstract: Abstract. Pulinets et al. (2007) document anomalous changes in the ionospheric total electron content (TEC) starting one week before the 16 October 1999 Hector Mine earthquake. The authors maintain that this TEC anomalous change is a precursor of the subsequent earthquake. In a previous paper, Afraimovich et al. (2004) excluded that TEC variations, which occurred before the Hector Mine earthquake, were induced by the preparation process of the seismic event. Thomas et al. (2012) reach similar conclusions by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 17 publications
3
40
0
1
Order By: Relevance
“…They concluded that the TEC changes were part of global‐scale variations driven by solar‐terrestrial interaction, and, therefore, not related to the localized seismic activity of the Hector Mine region. In a recent report, Masci [] confirmed the findings of Afraimovich et al . [] and Thomas et al .…”
Section: Previous Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…They concluded that the TEC changes were part of global‐scale variations driven by solar‐terrestrial interaction, and, therefore, not related to the localized seismic activity of the Hector Mine region. In a recent report, Masci [] confirmed the findings of Afraimovich et al . [] and Thomas et al .…”
Section: Previous Studiessupporting
confidence: 68%
“…[] and criticized their results. However, the authors did not reference the study of Masci [] that confirmed the conclusion of Thomas et al . [].…”
Section: Discussion Of Su Et Al Claimsmentioning
confidence: 90%
See 1 more Smart Citation
“…Comment 1: “The authors [ Su et al ., ] did not reference the study of Masci [] that confirmed the conclusion of Thomas et al . [].…”
Section: Reply To the Commentsmentioning
confidence: 88%
“…Among these methods are magnetic polarization ratio (see Thomas et al, 2009b;Masci, 2011aMasci, , 2012a, fractal characteristics of the geomagnetic field components (see Masci, 2010Masci, , 2013aMasci and Thomas, 2013), and eigenvalues of the principal component analysis (see Masci, 2011b). Reports of ionospheric earthquake-related disturbances were also investigated (see Masci, 2012dMasci, , 2013bThomas et al, 2012). Bearing in mind these findings, the reliability of earthquake precursory signals must be carefully investigated by means of independent data.…”
Section: Introductionmentioning
confidence: 99%